P4 Medicine Needs P4 Education - Cesario, Alfredo; Auffray, Charles; Russo, Patrizia; Hood, Leroy (Current Pharmaceutical Design, 2014)
This monographic issue of Current Pharmacological Design discusses extensively on the innovative paradigms for disease control in Active and Healthy Ageing. Wellness, as a status to be achieved and maintained in our lives, getting longer and hopefully healtier, is the new and comprehensive declination of “health” itself, leading the shaping of research and research policy in the health domain worldwide. Many of the contributions describe the state of the art –and beyond- approaches for the most common diseases based on the available medical knowledge; two, in particular (Bousquet J et al., Cesario A, et al.), extend to the innovative approaches defined in the framework of the holistic and integrative philosophy of the Predictive, Preventive, Personalized and Participatory (P4) Systems Medicine. The availability of more and more powerful technologies to extract data coupled with the inclusion of information coming from the nonstrictly- medical sphere of the patient/individual and his/her lifestyle along with the increase in computational power, will definitely set the stage for a paradigm-shift in bio-medicine with deep ethical and societal impact. The brief comment that follows speculates about the implications of this transition from the educational perspective taking stock of the direct experience of the Authors in the consultation process active in the scientific community.
Keywords: P4 medicine